469 Cooperation between checkpoint inhibitors targeting the PD-1/PD-L1 axis and ATRC-101, a novel clinical-stage candidate for the treatment of solid tissue malignancies. (10th December 2020) - Manning-Bog, Amy; DeFalco, Jeff; Scholz, Alexander; Aydin, Iraz; Vad, Nikhil; Czupalla, Cathrin; Chu, Felix; Velasco-Delgado, Mauricio; Harbell, Michael; Lugar-Supagay, Judevin; Leung, Yvonne; Lippow, Shaun; et al.
Abstract : Background: We have previously described ATRC-101, a fully human, engineered IgG1 antibody binding a tumor-restricted ribonucleoprotein (RNP) complex as its target. ATRC-101 is currently under evaluation in the clinic as a monotherapy for solid tumors. Following target engagement, ATRC-101 functions in an Fc-mediated fashion to deliver the target to the innate immune system, which modifies the tumor microenvironment and generates an adaptive immune response involving CD8+ T cells leading to anti-tumor activity in syngeneic mouse models. Binding of ATRC-101 appears restricted to malignant tissues in both mouse models and human, across a range of cancer histologic phenotypes, including carcinomas that are known candidates for anti-PD-1 treatment. In the EMT6 mouse model, representing a T cell-excluded phenotype in which anti-PD-1 agents display limited activity, ATRC-101 monotherapy was uniformly vigorous with persistent anti-tumor memory. When co-administered at a lower dose with anti-PD-1, the combination of therapy demonstrated a robust and heightened anti-tumor response relative to either agent dosed as monotherapy at similar concentrations. Methods: To gain insight into the mechanisms that contribute to the anti-tumor effect with combination therapy, in vivo experiments in the EMT6 syngeneic mouse model were performed to determine temporal and spatial patterns of infiltrates and assessed tumors by using whole exome sequencing following administration of ATRC-101 vs. vehicle control. Within naive human tumor samples, coincident immunoreactivities of ATRC-101 and PD-L1 were also characterized. Results: In mice treated with ATRC-101, analysis by immunofluorescence revealed a significant increase in the percentage of PD-1 reactive T cells within the tumor microenvironment. Elevated transcripts for PD-L1 also were detected in tumors from mice administered ATRC-101 vs baseline levels or vehicle control. When human tumor tissues were characterized for coincident expression of these targets, a high prevalence of ATRC-101 immunoreactivity was noted in both PD-L1 reactive and non-reactive tumor cores. Across multiple indications, ATRC-101 immunoreactivity was apparent in > 50% of PD-L1+ cores. Conclusions: In situ studies suggest the target of ATRC-101 may co-locate with PD-L1, and in vivo studies indicate that ATRC-101 administration increases PD-L1 transcripts and PD-1-positive infiltrates in mouse tumor. Altogether, our data support studies to combine ATRC-101 with agents targeting PD-1 in the clinical treatment of solid tissue malignancies. Acknowledgements: We acknowledge the significant effort and contributions of our colleagues from the clinical, in vivo pharmacology, translational sciences, in vitro pharmacology, and cell biology groups. This includes Mark Armanini, Erin Brosey, Chantia Carroll, Sean M. Carroll, Nicole Haaser, Benjamin Haugen, Dongkyoon Kim, Beatriz Millare, Yann Chong Tan, Danhui Zhang, and Patricia Zuno. Trial Registration: NCT04244552 Ethics Approval: The study was approved by WIRB (Western Institutional Review Board) on Jun 11, 2013. The WIRB study number is 20130121. Reference: DeFalco J, Harbell M, Manning-Bog A, et al. Non-progressing cancer patients have persistent B cell responses expressing shared antibody paratopes that target public tumor antigens. Clinical Immunology 2018; 187 :37–45.